Konsep Doa Puja Yesus menurut Kallistos Ware: Sebuah Doa Tanpa Henti - Lawolo, Aprianus (Sekolah Tinggi Teologi Kalvari Manado, 2023)
Abstract: Prayer is one of the important spiritual aspects of human life, especially for Christians. However, humans will only pray to Allah when they have urgent and important needs. Then, humans will expect Allah's help. That way, it is difficult for humans to always be in touch with God at all times. The purpose of this study is to explain what the true power of the Jesus puja prayer is and why it is an important part of the Christian faith based on a book written by Kallistos Ware of Diokleia. The method used by the author in this research is a literature study with a descriptive qualitative approach where the book